Rhupus : Étude de Deux Observations à Conakry, Guinée - Kaba, Condé; Salissou, Garba Mahaman; Moustapha, Niasse; Rama, Diallo (European Scientific Journal, ESJ, 2019)
Rhupus is a combination of RA and SLE clinical manifestations. It is a rare clinical entity which still remains controversial. We reported two (2) clinical cases which illustrate its existence by taking into account the review of medical literature. The diagnosis of both diseases was reached according to 2010 EULAR (European League Against Rheumatism)/ACR (American College of Rheumatology) classification criteria for RA and the 1997 ACR classification criteria for SLE. Although it is rare, the association of the two diseases is a real entity. Le rhupus est une association de polyarthrite rhumatoïde et de lupus érythémateux systémique. Il s’agit d’une entité clinique rare qui reste controversée. Nous en rapportons deux nouvelles observations de patients chez un homme de 48 ans et une femme de 26 ans qui illustrent, en confrontation avec les données de la littérature, la réalité de son existence. Le diagnostic de PR (Polyarthrite rhumatoïde) et de LES (lupus érythémateux systémique) était porté sur des arguments cliniques et paracliniques en accord avec les critères ACR (American College of Rheumatology) / EULAR (European League Against Rheumatism) 2010 pour la PR et ACR 1997 pour le LES. L’association de la polyarthrite rhumatoïde et du lupus est rare mais réelle.